Increasing water recovery during reclamation of treated municipal wastewater using bipolar membrane electrodialysis and fluidized bed crystallization. (December 2020) - AzadiAghdam, Mojtaba; Achilli, Andrea; Snyder, Shane A.; Farrell, James
Abstract: This research investigated the effectiveness of bipolar membrane electrodialysis coupled with fluidized bed crystallization and coagulation/flocculation with FeCl3 for removing potential membrane foulants from reverse osmosis (RO) concentrate solutions produced during reclamation of municipally treated wastewater. The goal of the treatment process was to produce water with low concentrations of potential foulants that could be subjected to a high recovery secondary RO process. Effluent from the secondary clarifier at a municipal wastewater treatment plant was treated by ultrafiltration and RO at a recovery of 60–65 %. The RO concentrate solution was then fed into a fluidized bed crystallization reactor operating at a pH value of 11.5. Calcium, magnesium, silica and dissolved organic matter were removed from the RO concentrate via precipitation of mineral solids on 60 mesh garnet sand. The acid and base utilized in the fluidized bed crystallization reactor was produced using bipolar membrane electrodialysis from the treated RO concentrate solution after polishing with coagulation/flocculation with FeCl3 . The treatment system was able to remove 84 % of Ca 2+, 93 % of Ba 2+, >99 % of Mg 2+, 80 % of total organic carbon (TOC), and 68 % of dissolved silica from the RO concentrate solutions. The product water produced by the system contained mostly Na +, Cl − and SO4 2- ions, with ≤ 10 mg/L Ca 2+ and SiO2, ≤ 2 mg/L TOC, and ≤ 1 mg/L Mg 2+ . The electrical energy for operating the bipolar membrane electrodialysis cell amounted to 110 kW h per kmol of acid and base produced, which translates to 3.5 kW h/m 3 of treated RO concentrate.